Molecular functions of the nuclear lamina in premature cell ageing - Foo, Mattheus Xing Rong (Nanyang Technological University, 2023)
Hutchinson-Gilford Progeria Syndrome (HGPS) is a premature ageing syndrome that manifests as early as 1 year of age. Patients exhibit severe phenotypes such as bone defects, cardiovascular complications, and a mean lifespan of 14 years. HGPS is caused by a silent heterozygous mutation that results in a mutant form of lamin A (LA), called progerin (PG). PG expression leads to severe cellular defects such as heterochromatin loss, impaired nucleocytoplasmic transport, telomeric DNA damage and a permanent growth arrest called cellular senescence. Although PG-induced phenotypes have been well characterised, the direct mechanism of PG and how its features contribute to HGPS remain unclear. Through a combination of genetic and pharmacological approaches, we identified and characterized 3 domains of PG that contribute to the disease etiology, 2 of which are novel. Further investigation demonstrated that these domains not only affect PG-induced phenotypes, but also PG protein levels. Collectively, our research provides unprecedented molecular insight into how different domains of PG contribute to premature cell ageing. Moreover, our results lay the foundation to systematically analyse how the over 400 different LMNA mutations result in cellular dysfunction and disease.